Frequency discrimination and literacy skills in children with mild to moderate sensorineural hearing loss. - Halliday, L; Bishop, D (2005)
It has been suggested that specific reading disability (SRD) may be attributable to an impaired ability to perceive spectral differences between sounds that leads to a deficit in frequency discrimination and subsequent problems with language and literacy. The objective of the present study was three-fold. We aimed to (a) determine whether children with mild to moderate sensorineural hearing loss were impaired in their ability to discriminate frequency, (b) assess the extent to which any such deficits may be due to an inability to use information derived from phase locking, and (c) examine whether frequency discrimination abilities were predictive of measures of word and nonword reading and nonword repetition. Difference limens for frequency (DLFs) were obtained for 22 children with mild to moderate hearing loss (SNH group) and 22 age-matched controls (CA group) at central frequencies of 1 kHz, where phase-locking information is available, and 6 kHz, where it is not. A battery of standardized tests of language and literacy was also administered. The SNH group exhibited significantly elevated DLFs at both 1 and 6 kHz relative to controls, despite considerable variability of thresholds in both groups. Although no group differences were found for receptive and expressive vocabulary, receptive grammar, and nonword reading, the SNH group performed worse than controls on word reading and nonword repetition, even though word reading scores were age-appropriate. Frequency discrimination abilities were associated with reading and nonword repetition across groups, but these correlations largely disappeared when the two groups were analyzed separately. Together, these results provide evidence for a dissociation between impaired frequency discrimination and relatively "spared" language and literacy in children with mild to moderate sensorineural hearing loss. These results cast doubt on the assertion that a deficit in frequency discrimination necessarily leads to marked deficits in the development of language and literacy.